(3ebGhO GdEfUGa aj eSGFd GdNdGa heYg eSGFd GdgOjI aj ePgH GdRjOjIs - (3TeS GdOjf LYaQ Hf CMeO Hf CHj jMji GdjeGfj GdRjOj,J (B573 (3g` s
(3ChdgG (B:s
(3SCdJe habfG Gdgd hEjGce ddHjGf hGdgOi Cf ChVM dce LedIef GdeSGFd GdJi NGdaJ ajgG GdeWQajI s
(3BNQgG (B:s
(3hgPG hGVM GdHjGf HMeO Gddg GdhGMO GdefGf , hUdi Gddg Ydi eMeO hBdg NjQ Bd hSde cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HBNQgG KdGKI hQbGJ PcQ ajgG NWHI GdYjOjf hNWHI GdfcGMs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3Yde GdcdGe (B78) s
Keywords: (3GdJhMjO hGdedd hGdfMds